Zinc-reinforced ZSM-5 subject to a rare-earth magnet and the presence of a legume yields considerable copper extraction - Khudr, Mouhammad Shadi; Baleca, Cristian; Alqahtani, Nasser; Alhassawi, Hassan; Garforth, Arthur; Tiddy, Gordon; Alfutimie, Abdullatif (PeerJ Materials Science, 2025)
Heavy-metal extraction using physically modified zeolites with reducing agents, subject to static magnetism and bioremediation, remains largely unexplored. Here, we partly gel-coated ZSM-5 pellets with zinc and tested their copper extraction from a polluted medium, with and without a neodymium magnet and/or a bio-trap (Vicia faba). The reinforced zeolite accrued the fastest extraction, outperforming the raw zeolite and the bio-trap, especially as time advanced. The reinforced zeolite, accompanied by the bio-trap, was the most effective over time, followed by having both companions (the magnet and the bio-trap) present. Having the magnet as a solo companion of the reinforced zeolite extracted more copper compared to the raw zeolite; but slightly yielded lesser than having the reinforced companionless. Interestingly, the bio-trap was a better companion than the magnet, and, after 20 min, having both companions was more beneficial than having the magnet alone, but less yielding than having the bio-trap alone in the long term, indicating a synergistic effect between the reinforced zeolite and the bio-trap. Further characterisation underscored stable yet differential ZSM-5 performance. Additionally, we plasma-sputtered ZSM-5 pellets with zinc, and tested their copper extraction under the magnet. That led to promising early results, despite a sharply deteriorated extraction efficacy over time, as more extraction was achieved than the cases of the raw zeolite, or the reinforced zeolite minus the magnet, with almost identical outcome compared to the reinforced zeolite plus the magnet. Our amalgamative approach provides novel user-friendly extraction methods, with high applicability potential across aquatic media and heavy metals.
Keywords: Zeolite; ZSM-5; Zeolite modification; Copper pollution; Faba bean; Heavy metal extraction; Super magnet